PEMILIHAN KARAKTER PADA PERMAINAN MULTIPLAYER ONLINE BATTLE ARENA DENGAN METODE AHP ( ANALYTIC HIERARCHY PROCESS ) - Melissa Vania Adelina; Jati Sasongko Wibowo (Universitas Teknokrat Indonesia, 2023)
Multiplayer Online Battle Arena ( MOBA ) game is an online game where players are placed into a specified area to battle with other players to reach a goal, be it in team or individually. Nowadays, there are kinds of Multiplayer Online Battle Arena ( MOBA ) game released and free to be accessed by everyone. This is causing developers aggressively looking for a way to compete. One of the way is releasing new characters. The impact is new players hardly choose proper character to play. Therefore, researcher will make a calculation using AHP ( Analytic Hierarchy Process ) method in choosing the proper characters to suit the player’s desire or skill. The methods will start with defining problems, determining hierarchy structures, and determining criteria as well as alternative choices. The result of the research is a decision support system to choose proper character accurately and efficiently.